The Development Of Web-Based Islamic Law E-Book Library Application in Sharia Faculty UIN Sultan Maulana Hasanuddin Banten - Wahyudi, M. Iman; Wahyu Wibowo, Eko; Mustaghfiroh, Mustaghfiroh; Muliasih, Wanda Tsania (Al Ahkam, 2023)
The purpose of this study is to develop a web-based e-book library application that can be accessed through a website application platform as a digital literacy activity service so that the literacy of the academic community of the Faculty of Sharia can be accommodated properly, which focuses on a collection of digital ebooks about Islamic law, so that it can mediate the excavation of knowledge about Islamic law anytime and anywhere without being hindered by space and time that focuses on  Collection of digital e-books on Islamic law. This research uses the Research Development method or also known as Research and Development (R&D), the results showed that there was an increase compared to the first validation there was an increase in the average value and criteria with a percentage value of 81%, the average score obtained was 4.05 with very good criteria compared to the initial validation which only got a percentage value of 78% of the average value obtained is 3.9